Is R&D financially restrained? Theory and evidence from Irish manufacturing - Spiros P. Bougheas; Holger Görg; Eric Strobl (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
We re-examine the effects of liquidity constraints on R&D investment. In our theoretical section we extend the neoclassical framework of investment in physical capital by introducing R&D and liquidity constraints. We analyse this issue empirically using firm-level data for R&D active manufacturing firms in the Republic of Ireland. Our results provide evidence that R&D investment is financially constrained which is in line with previous studies of US firms.
Keywords: 330; Betriebliche Forschung; Investition; Industrielle Forschung; Verschuldungsrestriktion; Verarbeitendes Gewerbe; Irland